Conductive paste with inorganic material added and preparation method thereof

By using a specific proportion of silver powder, modified molybdenum oxide and low-melting glass powder in the conductive silver paste of solar cells, and through reasonable proportioning and process processing of organic carriers, the problem of high contact resistance between conductive silver paste and silicon wafer is solved. , improves the photoelectric conversion efficiency and stability of solar cells, and is suitable for industrial production.

CN116564576BActive Publication Date: 2025-01-10NANTONG AISHENG NEW ENERGY TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310598628.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-24
Publication Date
2025-01-10
Estimated Expiration
2043-05-24

AI Technical Summary

Technical Problem

The existing conductive silver paste of solar cells cannot effectively reduce the contact resistance between the silver paste and the silicon wafer, affecting the photoelectric conversion efficiency and stability of the battery.

Method used

Conductive paste is prepared using 70-90% silver powder, 0.01-3% modified molybdenum oxide, 1-5% low melting point glass powder and 5-15% organic carrier, and processed through specific mass ratios and processes, including The preparation of organic carrier, the combination of low-melting glass powder and the dispersion of modified molybdenum oxide form a uniformly dispersed conductive paste, reducing contact resistance and improving adhesive performance.

Benefits of technology

It significantly reduces the contact resistance between the conductive silver paste and the silicon wafer, improves the photoelectric conversion efficiency and mechanical properties of solar cells, enhances the stability and adaptability of the conductive paste, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116564576B_ABST
    Figure CN116564576B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of solar cells, and in particular to the field of H01Q1 / 22, and more specifically to a conductive paste with added inorganic materials and a preparation method thereof. The raw materials for its preparation include, by mass percentage, 70-90% silver powder, 0.01-3% modified molybdenum oxide, 1-5% low-melting glass powder, and 5-15% organic carrier, and the preparation method includes the preparation of the organic carrier, the preparation of the low-melting glass powder, and the preparation of the modified molybdenum oxide, and the mixing and rolling of the slurry. The conductive paste prepared by the present invention has low contact resistance and good printing performance, and can improve the photoelectric conversion efficiency of solar cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solar cells, in particular to the field of H01Q1 / 22, and more specifically to a conductive paste added with inorganic materials and a preparation method thereof. Background Art

[0002] Solar energy is a clean energy with a wide range of sources. It is also a renewable energy source. The rational use of solar energy can effectively replace non-renewable resources such as coal, oil, etc., which is in line with the concept of green environmental protection and sustainable development. Solar cells can convert solar energy into electrical energy through photoelectric semiconductor thin films, and have very good application prospects. Solar cells can be mainly divided into three types: monocrystalline silicon solar cells, polycrystalline silicon thin film solar cells and amorphous silicon thin film solar cells. Among them, the conductive paste for crystalline silicon solar cells mainly includes positive electrode silver paste, back electrode silver paste and back electrode aluminum paste. The back electrode silver paste should have the following elements: low activity, reduce the reaction of glass powder and passivation film, avoid the formation of a large number of composite centers in the contact part between silver paste and silicon wafer, and increase the open circuit voltage of the cell; wide process window, adapt to low temperature sintering process; excellent adhesion and aging adhesion; of course, it also needs to have the characteristics required by the silver paste on the back of traditional crystalline silicon cells: good printing performance and low silver content. Among them, how to reduce the contact resistance between silver paste and silicon wafer is the focus of current research. Among them, due to the small size effect of nanomaterials, the melting point of oxide materials can be greatly reduced. By adding a very small amount of nanomaterials to the fine grid on the back side, the melting of silver in the slurry can be promoted, which can better enable the silver to contact the silicon wafer and reduce the contact resistance.

[0003] Prior art is that the patent CN108666005A discloses a conductive silver paste for photovoltaic cells, and its preparation raw materials include silver powder, organic carrier, surfactant, metal microcrystalline glass powder, wherein the metal microcrystalline glass powder is composed of antimony dioxide, lithium oxide, zinc oxide, tungsten oxide, molybdenum dioxide, etc., and the conductive paste can improve the photoelectric conversion efficiency of the battery, and the glass is not easy to flow during sintering; Prior art is that the patent CN109215837A discloses a silver conductive paste for solar cells and a preparation method thereof, and the preparation raw materials of the conductive paste include conductive silver powder, inorganic glass powder, organic carrier, nano zinc, wherein the conductive silver powder is a compound of spherical silver powder and flaky silver powder of a specific particle size, and the conductive paste can improve the energy conversion efficiency and maintain the bonding strength. However, the above conductive paste cannot guarantee a small contact resistance between the silicon wafer. Therefore, how to develop and prepare a conductive paste with a small contact resistance and excellent conductive performance has become a hot research issue in the field of solar cells. Summary of the invention

[0004] In order to solve the above problems, the first aspect of the present invention provides a conductive paste with added inorganic materials, the preparation raw materials of which include at least 70-90% silver powder, 0.01-3% modified molybdenum oxide, 1-5% low melting point glass powder, and 5-15% organic carrier in terms of mass percentage.

[0005] Preferably, the silver powder has a D50 particle size of 0.5-3 μm and a tap density of 4.0-6.0 g / cm 3 , with a specific surface area of ​​0.4-2.0m 2 / g.

[0006] Preferably, the raw materials for preparing the low melting point glass powder include 0 to 10 parts by weight of SiO 2 , 0~5 parts Al 2 O 3 , 20 to 35 copies B 2 O 3 , 5 to 15 parts of ZnO, 30 to 70 parts of PbO.

[0007] Preferably, the organic carrier includes ethyl cellulose, butyl carbitol, sorbitan monostearate, and cellulose acetate butyrate.

[0008] More preferably, the mass ratio of the ethyl cellulose, butyl carbitol, sorbitan monostearate, and cellulose acetate butyrate is (1-15):(2-15):(1-10):(2-6).

[0009] The organic carrier first needs to have a suitable viscosity, which is neither easy to flow nor difficult to flow. The viscosity decreases during use and can be restored after printing, so that the conductive paste and the silicon wafer have good contact performance and thus have a low contact resistance. Secondly, it has good thixotropy and has a good aspect ratio after screen printing. It also needs to have a relatively dispersed boiling point, which can be gradually volatilized and burned at high temperature to be completely removed, and it can ensure that the system does not agglomerate. The inventors found that when the organic carrier includes ethyl cellulose, butyl carbitol, sorbitan monostearate, and cellulose acetate butyrate, and the mass ratio is (1-15): (2-15): (1-10): (2-6), the above four compounds have hydrogen bonds within and between molecules. Therefore, the organic carrier can make the conductive paste have a suitable viscosity, so that the low-melting point glass powder can be evenly dispersed in the conductive paste, avoiding agglomeration, increasing the stability of the paste and the stability during screen printing. In addition, since sorbitan monostearate and the like contain a relatively long alkyl molecular chain, they can provide a certain thixotropy and also prevent the agglomeration of silver powder, thereby improving the photoelectric conversion efficiency of photovoltaic cells. After the conductive paste is dried, the organic carrier dispersed between the silver powder and the low-melting point glass powder can also form a network-like wrapping structure to further enhance the mechanical strength of the conductive paste.

[0010] As an implementable case, the mass ratio of the ethyl cellulose, butyl carbitol, sorbitan monostearate, and cellulose acetate butyrate may include 5:8:8:5, 5:7:5:4, 10:10:3:5, or 12:10:8:5.

[0011] Preferably, the raw materials for preparing the modified molybdenum oxide include molybdenum oxide and an organic solvent.

[0012] Preferably, the particle size of the molybdenum oxide is 10 nm-10 μm.

[0013] Further preferably, the mass ratio of the molybdenum oxide to the organic solvent is (1-3): (1-4).

[0014] As an implementable case, the mass ratio of the molybdenum oxide to the organic solvent may include 1:1, 3:2, 2:3, 1:2 or 3:4.

[0015] Preferably, the organic solvent is polyether-modified silicone.

[0016] Molybdenum oxide, as a hole transport layer material, has good stability and high work function in the air. Therefore, it can be used in the conductive paste to reduce the recombination of carriers, thereby reducing the contact resistance between the conductive paste and the silicon wafer. In addition, molybdenum oxide can also promote the melting of silver powder in the conductive paste system and promote better adhesion of the conductive paste after the screen printing process. The inventors selected molybdenum oxide with a particle size of 10nm-10μm in the system of the present invention. Due to the small size effect, the melting point of the material can be greatly reduced. By adding a very small amount of nanomaterials to the back fine grid, the melting of silver powder in the conductive paste is promoted. However, the dispersibility of molybdenum oxide in the system is poor. If it is not further The step treatment may cause precipitation and agglomeration. The inventors have found that the use of specific polyether-modified silicone can not only promote the dispersion of molybdenum oxide, but also form an emulsion-like state after dispersion with molybdenum oxide. In addition, the polyether-modified silicone can also improve the affinity of the organic carrier to silver powder and low-melting glass powder, thereby making the powder better dispersed in the slurry and improving the stability of the conductive slurry during the production process. When the mass ratio of molybdenum oxide to organic solvent is (1-3): (1-4), the stability of the system is optimal. If the content of molybdenum oxide is too much, a certain amount of precipitation will appear. If the content of polyether-modified silicone is too much, it will cause serious adsorption on the surface of the body and the printing thickness will be thin, resulting in a decrease in the efficiency of screen printing.

[0017] A second aspect of the present invention provides a method for preparing a conductive paste with added inorganic materials, comprising at least the following steps:

[0018] S1. Preparation of an organic carrier: ethyl cellulose, butyl carbitol, sorbitan monostearate, and cellulose acetate butyrate are uniformly mixed and stirred at a constant temperature, and then cooled to room temperature to obtain an organic carrier;

[0019] S2. Preparation of low melting point glass powder: SiO 2 , Al 2 O 3 , B 2 O 3 , ZnO and PbO are mixed evenly and put into a crucible for melting, then cold rolled, ball milled and dried to obtain low melting point glass powder;

[0020] S3, preparation process of modified molybdenum oxide: mixing an organic solvent with molybdenum oxide, and dispersing the mixture by ball milling in a planetary ball mill to obtain modified molybdenum oxide;

[0021] S4. Evenly mix the organic carrier, low melting point glass powder, modified molybdenum oxide and silver powder, and grind the mixture through a three-roll grinding agent to obtain a conductive paste with inorganic materials added thereto.

[0022] Preferably, in the step S1, the constant temperature stirring temperature is 80-100° C., the stirring time is 1-3 h, and the stirring speed is 100-300 rpm.

[0023] As an implementable case, the constant temperature stirring temperature may include 80°C, 85°C, 88°C, 90°C, 92°C, 95°C or 100°C; the stirring time may include 1h, 1.2h, 1.5h, 1.8h, 2.0h, 2.5h or 3.0h; the stirring speed may include 100rpm, 150rpm, 200rpm, 240rpm or 300rpm.

[0024] Preferably, in the step S2, the smelting temperature is 900-1200° C., the smelting time is 10-60 min, and the ball milling time is 3-6 h.

[0025] As an implementable case, the smelting temperature in the S2 step may include 900°C, 960°C, 1000°C, 1050°C, 1100°C or 1200°C; the ball milling time may include 3h, 4h, 4.5h, 5h or 6h.

[0026] Preferably, the ball milling dispersion time in step S3 is 1-3.5 h.

[0027] As an implementable example, the ball milling dispersion time in the S3 step may include 1h, 1.5h, 2h, 2.5h, 3h or 3.5h.

[0028] Preferably, the three-roll grinding in step S4 is performed 3-5 times.

[0029] As an implementable example, the number of times of three-roll grinding in step S4 may include 3, 4 or 5 times.

[0030] Beneficial Effects

[0031] (i) In the present invention, the conductive paste prepared by using specific mass percentages of raw materials: 70-90% silver powder, 0.01-3% modified molybdenum oxide, 1-5% low-melting point glass powder, and 5-15% organic carrier has a lower contact resistance, thereby improving the photoelectric conversion efficiency of solar cells.

[0032] (ii) In the present invention, by using low melting point glass powder, SiO 2 , Al 2 O 3 , B 2 O 3 The compound of ZnO and PbO not only has excellent bonding properties, allowing the conductive silver paste to adhere better to the silicon wafer, but also can cooperate with the organic carrier to make the conductive silver paste have better plasticity and mechanical properties.

[0033] (III) In the present invention, by using modified polyether silicone to modify molybdenum oxide of a specific particle size, and limiting the mass ratio of molybdenum oxide to modified polyether silicone to (1-3): (1-4), not only the contact resistance between the conductive paste and the substrate can be reduced, but also the affinity of the organic carrier to silver powder and low-melting-point glass powder can be improved, thereby improving the stability of the conductive paste during production and use.

[0034] (IV) In the present invention, by selecting specific organic carriers: ethyl cellulose, butyl carbitol, sorbitan monostearate, cellulose acetate butyrate, with a mass ratio of (1-15): (2-15): (1-10): (2-6), the agglomeration of silver powder can be prevented and the photoelectric conversion efficiency of the photovoltaic cell can be improved.

[0035] (V) In the present invention, an organic carrier, silver powder, low-melting-point glass powder and modified molybdenum oxide are slurried through a three-roll grinder to obtain a conductive paste with a viscosity of 20 kcps and a fineness of less than 10 μm. The preparation method is simple and suitable for industrial scale-up production. Moreover, the product has moderate viscosity and small fineness, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is the SEM image of silver powder.

[0037] Figure 2 This is a SEM image of silver powder and the modified molybdenum oxide described in Example 1 after sintering at 600°C.

[0038] Figure 3 This is a SEM picture of silver powder and the glass powder described in Example 1 after being blended and sintered at 600°C. DETAILED DESCRIPTION

[0039] Example 1

[0040] In a first aspect, the present embodiment provides a conductive paste with added inorganic materials, wherein the raw materials for preparing the conductive paste are as follows in terms of mass percentage: 86.75% silver powder, 0.25% modified molybdenum oxide, 3% low melting point glass powder, and 10% organic carrier.

[0041] The silver powder has a D50 particle size of 1-3 μm and a tap density of 4-6 g / cm 3 , with a specific surface area of ​​0.4-1.0m 2 / g, homemade.

[0042] The raw materials for preparing the modified molybdenum oxide are molybdenum oxide and polyether-modified silicone, and the mass ratio of molybdenum oxide to polyether-modified silicone is 1:1; the specification of the molybdenum oxide is 10nm-10μm, and it is purchased from Aladdin.

[0043] The raw materials for preparing the low melting point glass powder are as follows: 5 parts SiO 2 , 3 parts Al 2 O 3 , 25 copies B 2 O 3 , 10 parts ZnO and 50 parts PbO; the SiO 2 Specifications are CP (chemically pure), Al 2 O 3 Specifications: CP (chemically pure), B 2 O 3 The specification is CP (chemically pure), the specification of ZnO is CP (chemically pure), and the specification of PbO is CP (chemically pure).

[0044] The raw materials for preparing the organic carrier are ethyl cellulose (CAS No.: 9004-57-3), butyl carbitol (CAS No.: 112-34-5), sorbitan monostearate (CAS No.: 1338-41-6), and cellulose acetate butyrate (CAS No.: 9004-36-8); the mass ratio of ethyl cellulose, butyl carbitol, sorbitan monostearate, and cellulose acetate butyrate is 10:10:3:5.

[0045] The second aspect of the present embodiment provides a method for preparing a conductive paste with added inorganic materials, which comprises the following steps:

[0046] S1. Preparation of an organic carrier: Ethyl cellulose, butyl carbitol, sorbitan monostearate, and cellulose acetate butyrate were uniformly mixed and stirred at 85° C. and 200 rpm for 2 h, and then cooled to room temperature (25° C.) to obtain an organic carrier;

[0047] S2. Preparation of low melting point glass powder: SiO 2 , Al 2 O 3 , B 2 O 3 , ZnO and PbO are mixed evenly and put into a crucible and smelted at 1050°C for 30 minutes, then cold rolled, ball milled for 5 hours, and dried to obtain low melting point glass powder;

[0048] S3, preparation process of modified molybdenum oxide: mixing an organic solvent with molybdenum oxide, and dispersing the mixture by ball milling in a planetary ball mill for 2 hours to obtain modified molybdenum oxide;

[0049] S4. The organic carrier, low melting point glass powder, modified molybdenum oxide and silver powder are uniformly mixed, and the slurry is rolled by three-roll grinding agent for 4 times to obtain the conductive slurry with added inorganic material.

[0050] The SEM image of the silver powder is as follows Figure 1 described.

[0051] The SEM image of the silver powder and the modified molybdenum oxide after sintering at 600° C. is as follows: Figure 2 shown.

[0052] The SEM image of the silver powder and the glass powder after sintering at 600° C. is as follows: Figure 3 shown.

[0053] Example 2

[0054] In a first aspect, the present embodiment provides a conductive paste with added inorganic materials, wherein the raw materials for preparing the conductive paste are as follows in terms of mass percentage: 86.5% silver powder, 0.5% modified molybdenum oxide, 3% low melting point glass powder, and 10% organic carrier.

[0055] The silver powder has a D50 particle size of 1-3 μm and a tap density of 4-6 g / cm 3 , with a specific surface area of ​​0.4-1.0m 2 / g, homemade.

[0056] The raw materials for preparing the modified molybdenum oxide are molybdenum oxide and polyether-modified silicone, and the mass ratio of molybdenum oxide to polyether-modified silicone is 1:1; the specification of the molybdenum oxide is 10nm-10μm, and it is purchased from Aladdin.

[0057] The raw materials for preparing the low melting point glass powder are as follows: 5 parts SiO2 , 3 parts Al 2 O 3 , 25 copies B 2 O 3 , 10 parts ZnO and 50 parts PbO; the SiO 2 Specifications are CP (chemically pure), Al 2 O 3 Specifications: CP (chemically pure), B 2 O 3 The specification is CP (chemically pure), the specification of ZnO is CP (chemically pure), and the specification of PbO is CP (chemically pure).

[0058] The raw materials for preparing the organic carrier are ethyl cellulose (CAS No.: 9004-57-3), butyl carbitol (CAS No.: 112-34-5), sorbitan monostearate (CAS No.: 1338-41-6), and cellulose acetate butyrate (CAS No.: 9004-36-8); the mass ratio of ethyl cellulose, butyl carbitol, sorbitan monostearate, and cellulose acetate butyrate is 10:10:3:5.

[0059] The second aspect of the present embodiment provides a method for preparing a conductive paste with added inorganic materials, which comprises the following steps:

[0060] S1. Preparation of an organic carrier: Ethyl cellulose, butyl carbitol, sorbitan monostearate, and cellulose acetate butyrate were uniformly mixed and stirred at 85° C. and 200 rpm for 2 h, and then cooled to room temperature (25° C.) to obtain an organic carrier;

[0061] S2. Preparation of low melting point glass powder: SiO 2 , Al 2 O 3 , B 2 O 3 , ZnO and PbO are mixed evenly and put into a crucible and smelted at 1050°C for 30 minutes, then cold rolled, ball milled for 5 hours, and dried to obtain low melting point glass powder;

[0062] S3, preparation process of modified molybdenum oxide: mixing an organic solvent with molybdenum oxide, and dispersing the mixture by ball milling in a planetary ball mill for 2 hours to obtain modified molybdenum oxide;

[0063] S4. The organic carrier, low melting point glass powder, modified molybdenum oxide and silver powder are uniformly mixed, and the slurry is rolled by three-roll grinding agent for 4 times to obtain the conductive slurry with added inorganic material.

[0064] Comparative Example 1

[0065] The first aspect of the present comparative example provides a conductive paste with added inorganic materials, and the raw materials for preparing the conductive paste are as follows: 87% silver powder, 3% low melting point glass powder, and 10% organic carrier in terms of mass percentage.

[0066] The silver powder has a D50 particle size of 1-3 μm and a tap density of 4-6 g / cm 3 , with a specific surface area of ​​0.4-1.0m 2 / g, homemade.

[0067] The raw materials for preparing the low melting point glass powder are as follows: 5 parts SiO 2 , 3 parts Al 2 O 3 , 25 copies B 2 O 3 , 10 parts ZnO and 50 parts PbO; the SiO 2 Specifications are CP (chemically pure), Al 2 O 3 Specifications: CP (chemically pure), B 2 O 3 The specification is CP (chemically pure), the specification of ZnO is CP (chemically pure), and the specification of PbO is CP (chemically pure).

[0068] The raw materials for preparing the organic carrier are ethyl cellulose (CAS No.: 9004-57-3), butyl carbitol (CAS No.: 112-34-5), sorbitan monostearate (CAS No.: 1338-41-6), and cellulose acetate butyrate (CAS No.: 9004-36-8); the mass ratio of ethyl cellulose, butyl carbitol, sorbitan monostearate, and cellulose acetate butyrate is 10:10:3:5.

[0069] The second aspect of this comparative example provides a method for preparing a conductive paste with added inorganic materials, which comprises the following steps:

[0070] S1. Preparation of an organic carrier: Ethyl cellulose, butyl carbitol, sorbitan monostearate, and cellulose acetate butyrate were uniformly mixed and stirred at 85° C. and 200 rpm for 2 h, and then cooled to room temperature (25° C.) to obtain an organic carrier;

[0071] S2. Preparation of low melting point glass powder: SiO 2 , Al 2 O 3 , B 2 O 3 , ZnO and PbO are mixed evenly and put into a crucible and smelted at 1050°C for 30 minutes, then cold rolled, ball milled for 5 hours, and dried to obtain low melting point glass powder;

[0072] S3, the organic carrier, low melting point glass powder and silver powder are mixed evenly, and the slurry is rolled by three-roll grinding agent for 4 times to obtain the conductive slurry with added inorganic material.

[0073] Performance Evaluation

[0074] 1: Contact resistance test

[0075] Test object: Conductive paste with inorganic materials added prepared in Example 1-2 and Comparative Example 1

[0076] Test method: Use TLM contact resistance tester to test the contact resistance of the conductive paste and record the results in Table 1

[0077] Table 1

[0078] Contact resistance Rc(Ω) Example 1 0.9 Example 2 1.13 Comparative Example 1 1.84

[0079] The above experimental data and the contents in the drawings of the specification indicate that the addition of modified molybdenum oxide can promote the melting of silver powder in the system, thereby reducing the resistance of the conductive paste prepared by the present invention.

Claims

1. A conductive paste with added inorganic material, characterized in that: The raw materials for preparation include at least 70-90% silver powder, 0.01-3% modified molybdenum oxide, 1-5% low melting point glass powder, and 5-15% organic carrier according to mass percentage; The sum of the mass percentages of the above components is 100%; The raw materials for preparing the low-melting-point glass powder include 0 to 10 parts of SiO2, 0 to 5 parts of Al2O3, 20 to 35 parts of B2O3, 5 to 15 parts of ZnO, and 30 to 70 parts of PbO according to the weight percentage; The raw materials for preparing the modified molybdenum oxide include molybdenum oxide and an organic solvent; The particle size of the molybdenum oxide is 10 nm-10 μm; The mass ratio of the molybdenum oxide and the organic solvent is (1-3): (1-4); The organic solvent is polyether-modified silicone.

2. The conductive paste containing inorganic materials according to claim 1, characterized in that: The organic carrier includes ethyl cellulose, butyl carbitol, sorbitan monostearate and cellulose acetate butyrate.

3. The conductive paste containing inorganic materials according to claim 2, characterized in that: The mass ratio of the ethyl cellulose, butyl carbitol, sorbitan monostearate and cellulose acetate butyrate is (1-15): (2-15): (1-10): (2-6).

4. A method for preparing a conductive paste containing inorganic materials according to any one of claims 2 to 3, characterized in that: At least the following steps are included: S1. Preparation of an organic carrier: ethyl cellulose, butyl carbitol, sorbitan monostearate, and cellulose acetate butyrate are uniformly mixed and stirred at a constant temperature, and then cooled to room temperature to obtain an organic carrier; S2. Preparation of low melting point glass powder: SiO2, Al2O3, B2O3, ZnO and PbO are mixed evenly and put into a crucible for melting, followed by cold rolling, ball milling and drying to obtain low melting point glass powder; S3, preparation process of modified molybdenum oxide: mixing an organic solvent with molybdenum oxide, and dispersing the mixture by ball milling in a planetary ball mill to obtain modified molybdenum oxide; S4. Evenly mix the organic carrier, low melting point glass powder, modified molybdenum oxide and silver powder, and slurry the mixture through a three-roll mill to obtain a conductive paste with inorganic materials added thereto.

5. The method for preparing a conductive paste with added inorganic materials according to claim 4, characterized in that: In the step S1, the constant temperature stirring temperature is 80-100°C, the stirring time is 1-3h, and the stirring speed is 100-300rpm; in the step S2, the melting temperature is 900-1200°C, the melting time is 10-60 min, and the ball milling time is 3-6h.

Citation Information

Patent Citations

  • Conductive silver paste used for photovoltaic cells

    CN108666005A

  • A silver conductive paste for solar cell and a preparation method thereof

    CN109215837A

  • Solar energy battery electrode-conducting silver slurry containing micron-size mixed silver powders

    CN102592710A

  • Anti-oxidation silver paste for car windshield glass and preparation method thereof

    CN109785991A